Defining the ecological strategies of phytoplankton associated bacteria - Amaranta Focardi; Anna R. Bramucci; Penelope Ajani; Abeeha Khalil; Jean-Baptiste Raina; Justin R. Seymour (Nature Communications)
Abstract Ecological interactions between phytoplankton and bacteria govern the productivity and biogeochemistry of aquatic ecosystems. However, our understanding of these partnerships primarily comes from laboratory-based model systems, meaning that little is known about the establishment and dynamics of these interactions. Here, we tracked the development of the microbiome of 15 newly isolated phytoplankton species for 400 days. After only 20 days, each phytoplankton harboured a unique bacterial assemblage. Within these assemblages, we identify (i) specialist phytoplankton associates, which are bacteria that establish long-term interactions with 1-2 phytoplankton strains; (ii) generalists, which are associated with 3 or more phytoplankton strains; and (iii) transients, which do not develop sustained associations with any phytoplankton strains. Compared to transients, the generalists and specialists are enriched in genes involved in chemotaxis, vitamin synthesis, secondary metabolite production and the ability to uptake specific phytoplankton-derived compounds. Moreover, generalists display greater potential to move between hosts and release antimicrobials. Finally, examination of co-occurrence patterns in oceanographic time-series revealed that generalists and specialists mirror their phytoplankton partner’s abundance in the environment. The divergent genomic characteristics of these discrete bacterial categories highlight different ecological strategies that likely shape phytoplankton microbiomes.